Recent Advances in Quantum Dots for Photocatalytic CO2 Reduction: A Mini-Review - Park, Young Ho; Murali, G.; Modigunta, Jeevan Kumar Reddy; In, Insik; In, Su-Il (Frontiers in Chemistry, 2021)
Solar energy–driven carbon dioxide (CO2) reduction to valuable solar fuels/chemicals (e.g., methane, ethanol, and carbon monoxide) using particulate photocatalysts is regarded as one of the promising and effective approaches to deal with energy scarcity and global warming. The growth of nanotechnology plays an eminent role in improving CO2 reduction (CO2R) efficiencies by means of offering opportunities to tailor the morphology of photocatalysts at a nanoscale regime to achieve enhanced surface reactivity, solar light absorption, and charge separation, which are decisive factors for high CO2R efficiency. Notably, quantum dots (QDs), tiny pieces of semiconductors with sizes below 20 nm, offering a myriad of advantages including maximum surface atoms, very short charge migration lengths, size-dependent energy band positions, multiple exciton generation effect, and unique optical properties, have recently become a rising star in the CO2R application. In this review, we briefly summarized the progress so far achieved in QD-assisted CO2 photoreduction, highlighting the advantages of QDs prepared with diverse chemical compositions such as metal oxides, metal chalcogenides, carbon, metal halide perovskites, and MXenes.